Estudo de catalisadores Pd-a% - Nb2O5 / Al2O3 na reação de síntese de metil isobutil cetona (MIBK) - Dutra, Marcia Regina Aparecida (2000)
The main aim of this thesis was studied the niobium oxide promoting effect on Pd/A^Os catalyst at methyl isobutyl ketone (MIBK) synthesis by acetone and hydrogen. For this purpose, 0,7%Pd-x%Nb2Oí/A.l2O3 (x = 0, 5, 10 e 20 %) catalysts were prepared. The calcined catalysts were characterized by atomic absorption, N2-isotherms (Sbet), diffuse reflectance spectroscopy (DRS), and temperatura programmed reduction (TPR). The catalytic sites were characterized by chemisorption and temperatura programmed desorption of NH3 (acidic sites) and H2 (metallic sites). The DRS spectra revealed the presence of well dispersed PdO and/or PdClx(H2O)y species. The catalyst with 10 % of Nb2Os presented the highest acidity per gramme of catalyst. The NH3-chemisorption and desorption showed an acidity increase with the chlorine presence, palladium addition, and SMSI effect. The H2-chemisorption and desorption results revealed that catalysts with well dispersed palladium were prepared, which the highest was at 93% with the P5NA catalyst. The reaction profiles showed that the P20NA catalyst had the highest MIBK yield (60%), which demonstrates the great potential of the studied system for the reaction. These results indicated that the catalysts stabilities and the MIBK yields are related strongly with the catalysts acidities.